Poetry, Resistance, World-Literature: Adília Lopes and Marie Buck - Medeiros, Paulo de (eLyra: Revista da Rede Internacional Lyracompoetics, 2019)
This essay begins an exploration of how poetry functions within the field of world-literature, drawing specifically on the Warwick Research Collective’s Combined and Uneven Development: Towards a New Theory of World-Literature and reflecting comparatively on the poetry of Adília Lopes and Marie Buck. Even though there are many differences between the two authors and their works, one common feature of their poetics is the deployment of poetry as a form of resistance. As such, both can be seen as especially significant so as to probe into the condition of poetry within a conceptualization of world-literature understood as the literature of the capitalist world-system. As the essay argues, both Adília Lopes and Marie Buck register specific conditions of oppression within a capitalist, patriarchal, society and offer ways to contest them.